Reducing EFL Speaking Anxiety via Blended Mentoring: The Role of Rhetorical Modeling - Ilhamuddin Muhammad; Punaji Setyosari; Otto Fajarianto (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Public speaking anxiety remains a persistent challenge for English as a Foreign Language (EFL) learners, limiting their ability to communicate effectively in academic settings. Although various interventions have been proposed to address this issue, limited attention has been given to integrating rhetorical modeling within a blended mentoring framework that combines cognitive guidance with continuous affective support. This study therefore investigates the potential of blended mentoring enriched with rhetorical modeling to reduce public speaking anxiety among junior secondary EFL students. A pre-experimental one-group pre-test and post-test design was employed involving nine students selected through purposive sampling. The intervention consisted of face-to-face mentoring sessions complemented by asynchronous video-based feedback delivered through messaging platforms. Public speaking anxiety was measured using an adapted anxiety scale before and after the intervention, and the data were analyzed using a paired-sample t-test. The results revealed a statistically significant reduction in students’ anxiety levels (p < 0.001), with the mean score decreasing from 78.44 to 64.11. The calculated effect size (Cohen’s d = 2.37) indicated a very large practical effect. These findings provide preliminary evidence that a blended mentoring approach integrating rhetorical modeling may contribute to reducing public speaking anxiety by supporting learners through continuous feedback, guided rehearsal, and structured speech organization. The study contributes to the EFL speaking literature by proposing a process-oriented mentoring framework that integrates rhetorical modeling with blended feedback to simultaneously address the cognitive and affective dimensions of public speaking. Further research employing controlled experimental designs is recommended to confirm these findings